Flexible and Controllable Metadevice Using Self-Assembly MEMS Actuator - Xu, Ruijia; Lin, Yu-Sheng (Nano letters, 2021)
In this work, an actively tunable optical metadevice is proposed to realize multifunctional application by integrating self-assembly electrothermal actuator (ETA) and magnetic metamaterial. The released frame of ETA can control the deformed height of the metamaterial plate and then provide high robustness. By driving the external electromagnetic field, the metamaterial plate is actuated and rotated by a magnetic force to manipulate the incident electromagnetic response. The transmission intensities of the metadevice can be gradually increased to characterize “on” and “off” states. Along with the inputs of light source and magnetic field, the transmission results of the metadevice could provide the output of time-difference optical signal and then carry with digital information in the further optical logic operation. Such an actuation method provides an ideal platform for actively tunable metamaterial with a large tilt angle and displacement. MEMS-based metamaterial is a strategy to open an avenue for optical communication, 3D imaging, and optical logic switching applications.